EFFECTS OF TOXIC AND POTENTIALLY TOXIC CHEMICAL ELEMENTS AT RISK OF HEART ARRHYTHMIAS IN CHILDREN - Анна Валериевна Дубовая (The Publishing House Medicine and Enlightenment, 2017)
In the last decade, it gains relevance, but still not fully resolved issue of the possible impact of toxic and potentially toxic chemical elements on the onset and progression of cardiovascular diseases associated with heart arrhythmias. Objective - to determine the level of concentration of toxic and potentially toxic chemical elements, which determines the risk of the heart arrhythmias. Materials and methods. The study involved 255 children, aged from 6 to 17 years residing in the Donbass region: 198 children (107 boys and 91 girls) with a variety heart arrhythmias and 57 healthy children (31 boys and 26 girls). All children carried spectral multivariate analysis hair assessing content of 14 chemical elements: 8 toxic (lead, barium, cadmium, bismuth, aluminum, mercury, beryllium, thallium) and 6 potentially toxic (strontium, nickel, lithium, antimony, arsenic, vanadium) by methods of atomic emission spectrometry in inductively coupled plasma and atomic absorption spectrometry with electrothermal atomization. Results. The observed concentration of lead, barium, aluminum, strontium, nickel, arsenic, was below the maximum allowable level. As a result of ROC-analysis found that levels of lead above 0,272 mg/kg in 73 % of cases occur heart arrhythmias. In 78 % of barium levels above 0,571 mg/kg is a risk factor of heart arrhythmia. When aluminum levels above 19,442 mg/kg in 74 % of cases occur heart arrhythmia. Excess strontium concentration higer than 3,318 mg/kg and nickel concentration higer than 0,462 mg/kg in 76 % of cases leads to heart arrhythmia. At the level of arsenic above 0,184 mg/kg in 77 % of cases there is an arrhythmia. Conclusion. The average concentration of the identified toxic (lead, barium, cadmium, bismuth, aluminum, mercury) and potentially toxic (strontium, nickel, lithium, antimony, arsenic) chemical elements in children with heart arrhythmias was higher (statistically significant for lead, barium, cadmium, strontium and nickel) than in healthy children. A significant level of concentration in the hair of lead, barium, aluminum, strontium, nickel, arsenic as a risk of the heart arrhythmias are determine.